Comparative study of the effects of VBT training with different velocity loss thresholds on lower limb explosive force of adolescent sprinters - Wang, J.; Zeng, Z.; Lu, Q.; Yuan, S.; Chai, Y. (Frontiers in Physiology, 2025)
Objectives: This study aimed to investigate the effects of velocity-based training (VBT) on lower-limb explosive performance in adolescent sprinters and to compare the training adaptations induced by different velocity loss thresholds (VLT).